Problems of differential diagnosis of community-acquired pneumoni - O. V. Fesenko (Медицинский совет, 2015)
Differential diagnosis of community-acquired pneumonia is often a challenge for physician as it requires a deep knowledge not only in pulmonology but also in cardiology, surgery, neurology. The article uses real examples showing various disieases simulating CAP to examine the reasons for underdiagnosis of pneumonia.